Combustion Wave Structure of the Ammonium Dinitramide‐Based Ionic Liquid Propellant. Issue 2 (28th November 2022) - Ide, Yuichiro; Izato, Yu‐ichiro; Koshi, Mitsuo; Miyake, Atsumi; Habu, Hiroto; Tokudome, Shinichiro
Abstract: The ammonium dinitramide‐based ionic liquid propellant (ADN‐based ILP), which is a mixture of ADN, monomethylamine nitrate (MMAN), and urea, is a low toxic monopropellant with a higher performance than that of hydrazine. To clarify the combustion wave structure of ADN‐based ILP, which has low volatility, we focused on the relationship between the phase state and temperature in ADN‐based ILP combustion and on clarifying the gas‐liquid phase reaction. The combustion still image and temperature distribution of ADN‐based ILP were obtained by strand burning tests with a high‐speed camera. As a result, two stages of the stable temperature region were found in the gas‐liquid phase. The pressure dependences of temperature in the stable temperature region were compared with the vapor pressure curves of some chemical substances and with the decomposition temperatures of ADN, MMAN, and urea. Then, it was inferred that the thermal decompositions of ADN, MMAN, and urea, as well as the evaporation of urea had occurred at the first stage of the stable temperature region. Also, it was found that the liquid ammonium nitrate had been dissociated at the second stage of the stable temperature region. For a report on the existence of dissociation products of MMAN and urea vapor on the burning surface at 1.2 MPa, the dissociation of MMAN and evaporation of urea would occur at the first stage of the stable temperature region at 1.2 MPa. As stated above, the combustion wave structure of ADN‐based ILP was developed at 1.2 MPa. Abstract :